Stereospecific Distribution Pattern of Fatty Acids in Triglycerides: A Comparative Review of Human, Bovine, Bubaline, Caprine, and Equine Milk Fat. - Rout, Pavel; Sharma, Vivek; Arora, Sumit (Indian Journal of Dairy Science, 2024)
Major lipid fraction of milk fat is triacylglycerol (TAG) representing about 98% of total lipids. TAG contains a glycerol backbone and three fatty acids. These three fatty acids are positioned at sn-1, sn-2 & sn-3 position in glycerol backbone and the positioning is called as stereospecific positioning. This stereospecific positioning mainly effects the lipid metabolism of dietary lipids. During the digestion of TAG in human beings, lipase preferably attacks the TAG at sn-1 or sn-3 positions resulting in the release of free fatty acids along with sn-2 monoacylglycerol. It has been reported that saturated fatty acids are mainly esterified in sn-2 position whereas unsaturated fatty acids are esterified in sn-1 and 3 positions. The fatty acid distribution among the three sn-positions of the glycerol backbone is non-random. The non-random distribution is a result of the specificity of different enzymes during TAG biosynthesis. The distribution of fatty acids depends upon species, feed, season and lactation period. The stereospecific arrangement of fatty acids in fat also influences some physical properties of fats and oils like crystallization and melting properties. The stereospecific arrangement of milk fat is generally studied by using different lipases along with separation techniques and finally chromatography or spectroscopy. Understanding these aspects can aid in identifying the origin of the fat, detecting potential adulteration of different other species of milk, and predicting nutritional value of different species’ milk based on differences in the form of sn-2-MAG and free fatty acids.